Latin medical terminology: textbook - Петрова, Г. Вс. Галина Всеволодовна (Textbook, 2023)
The textbook contains a brief overview of the Latin language role, a compact presentation of those sections of Latin grammar needed to understand medical terminology, sections on anatomical terminology, pharmaceutical chemistry, pharmacological and clinical terminology. The novelty of the textbook consists of unconventional structure without division into separate classes, which refl ects the current trends in free planning of classes by the teacher and the university. An unusually detailed explanation of the theory, grammatical and prescription samples, as well as greatly varied practical tasks help students to understand the terminology, and provide an opportunity to study the material independently. The appendix presents glossaries of anatomical nomenclature and terminology, historical materials, international Latin abbreviations and symbols, etymology of some anatomical terms, etc. The textbook meets the requirements of curriculum of Latin Medical Terminology course; it is furnished with visual tables, a system of tasks that prompts recourse to modern technologies and information sources, includes a lot of cultural information, is written in a simple and easy language. The presentation of material complies with modern psychological, pedagogical and methodological requirements. The latest international standards are also taken into account. The publication can be used in all medical universities, regardless of specialization or curriculum.